Bildung zur Solidarität: Welchen Beitrag leistet die christliche Religion? - Könemann, Judith (European Journal of Mental Health, 2014)
Solidarity Education: How the Christian Religion Can Contribute to It?: Solidarity is a fashionable term nowadays. It can be encountered in almost all areas of social coexistence; mostly in contexts where (more) solidarity is being called for or in discussions about cohesion in modern society. While this has led to some devaluation in the meaning of the word, there are two underlying questions to be answered: 1. What is exactly behind the term ‘solidarity’? 2. To what extent are individuals able to display solidarity by themselves and can solidarity be taught with the help of training and educational processes? The present paper discusses both questions. The main focus will be placed on the connections between acts of solidarity and religious attitude or conviction and on pointing out how religion contributes to the learning process of solidarity. In this respect the thesis statement of the present study is as follows: religion is not a prerequisite for the ability of solidarity; nevertheless, due to the strong relationship between Christianity and solidarity, it can provide an important source of motivation. Following an extensive review of terminology, the study goes on to discuss pro-solidarity, which is a special form of solidarity aimed at the interest of others. In the next section a number of biblical examples are analysed in order to examine the relationship between solidarity and the Christian religion in detail and to identify solidarity as a religious and moral duty based on the principle of mercy. After these introductory theological considerations we will turn to presenting some practical perspectives in learning solidarity and argue for the unparalleled credibility and potential that Christianity has in teaching and consolidating solidarity. Although the Christian religion is not an indispensable medium of teaching such patterns of behaviour, it can make a significant contribution to the training and educational processes involved.